Effects of biochar derived from the pyrolysis of either biosolids, manure or spent coffee grounds on the growth, physiology and quality attributes of field-grown lettuce plants - Christou, Anastasis; Stylianou, Marinos; Georgiadou, Egli C.; Gedeon, Stella; Ioannou, Andreas; Michael, Costas; Papanastasiou, Panos; Fotopoulos, Vasileios; Fatta-Kassinos, Despo (My University, 2022)
The positive effects of biochar applied as soil conditioner for boosting soil fertility and thus plant growth are sufficiently documented, mostly through in-situ experimentation. This field study evaluated the effects of soil amendment (5% v/v) with distinct types of biochar (biosolids-derived biochar, BDB; cattle manure-derived biochar, MDB; spent coffee grounds-derived biochar, SCGDB) on the growth, physiology and quality attributes of lettuce (Lactuca sativa L.) plants grown in sandy clay loam-textured soil, under temperate climatic conditions. Peat moss (PM) was also used, to serve as internal control due to its wide use. Plants grown on MDB-amended soil showed a significant increase of biomass production rate, evident through elevated mean fresh and dry weight values compared with all other treatments. Increased growth was also found in BDB treatment, though failed to reach significance. None of the treatments impacted the photosynthetic pigment content, however they did reduce the nitrates content in leaves. Leaves sampled from BDB and MDB treatments showed reduced soluble solids content (SSC) and titratable acidity (TA), and increased sucrose content. MDB-treated plants showed increased fructose content while BDB-treated plants showed increased total soluble sugar and total phenolics content. Moreover, plants grown in MDB- and BDB-amended soil showed increased total antioxidant capacity, despite maintaining ascorbic acid content in values similar to control. SCGDB and PM treatment did not affect any of the parameters tested. Overall, results showed that BDB and MDB applied as soil amendments may serve as means for enhancing the growth, and partially the nutritional value of lettuce plants.
Keywords: Antioxidant capacity; Plant growth; Biochar; Carbohydrate; Lettuce; Photosynthetic pigment